2002
DOI: 10.1161/01.cir.0000041046.32962.86
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Between Obesity and Insulin Resistance in the Association With C-Reactive Protein

Abstract: Background-Plasma C-reactive protein (CRP) concentrations are increased in obese and/or hyperinsulinemic individuals.The goal of this study was to determine if the relation between insulin resistance and CRP was independent of obesity. Methods and Results-Plasma CRP concentrations were measured before and after 3 months of calorie restriction in 38 healthy, obese women. Steady-state plasma glucose (SSPG) concentration during a 180-minute infusion of octreotide, glucose, and insulin was used to stratify partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
194
6
13

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(237 citation statements)
references
References 35 publications
23
194
6
13
Order By: Relevance
“…CRP (a strong predictor of cardiovascular disease) is lowered following improvements in insulin sensitivity. 38 Indeed, CRP was reduced by wk 16 in this study and the relatively low glycemic load of both diets may have augmented this reduction. 39 The modest improvements in liver function markers occurred despite subjects being within normal range at baseline.…”
Section: Discussionmentioning
confidence: 57%
“…CRP (a strong predictor of cardiovascular disease) is lowered following improvements in insulin sensitivity. 38 Indeed, CRP was reduced by wk 16 in this study and the relatively low glycemic load of both diets may have augmented this reduction. 39 The modest improvements in liver function markers occurred despite subjects being within normal range at baseline.…”
Section: Discussionmentioning
confidence: 57%
“…3,10,19,[36][37][38] A study of healthy premenopausal women who completed a 1-y weight loss programme achieved a minimum 10% loss of weight and a decrease in cytokine (IL-6 and TNF-a) produc- CRP reduction following gastric bypass surgery C Holdstock et al tion. 34 Medical treatment with sibutramine or orlistat for 6 months achieved a reduction in CRP despite less weight loss (2-5.4%).…”
Section: Discussionmentioning
confidence: 99%
“…9 In contrast, in a study of obese women in which CRP was measured before and after 3 months of reduced energy intake, the relation between CRP concentrations and insulin resistance appeared independent of obesity. 10 The medical treatment of obesity, in particular morbid obesity (BMI Z40 kg/m 2 ), is unsatisfactory and has led to the increased use of surgery worldwide. 11 Roux-en-Y gastric bypass (RYGBP) causes a marked reduction in adipose tissue mass, 12 alters adipose tissue regulatory hormones 13 and reduces morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been shown that not all obese subjects have high levels of C-reactive protein (CRP), but only those who are insulin resistant, 3 suggesting a strong link between insulin resistance and inflammation.…”
Section: Introductionmentioning
confidence: 99%